Regulacja prawna agroturystyki – uwagi de lege ferenda - KAPAŁA, ANNA (Wydawnictwo Naukowe UAM, 2010)
The aim of this discussion was to make an attempt at an outline of a legal concept of agritourism, which is manifested in the formulated proposals de lege ferenda. When realising such a specified goal, the Author in the first part of the paper indicates weak points of binding legal solutions concerning agritourism, while in the second part presents proposals for their improvement. The legal regulation in Italy was a reference point for this evaluation and proposed changes. The Author proposed e.g. the introduction of a legal definition of agritourism and a broad definition of agricultural activity, covering agritourism and other activities of non condition of being connected with the basic agricultural activity. It is also necessary to change regulations concerning the direct sale of products processed on the farm, as well as introduce legal protection for the term “agritourism” and systematise scattered regulations into one legal act (the act on agritourism).

La trattazione tenta di delineare un concetto giuridico di agriturismo, di cui sono espressione le proposte de lege ferenda formulate nell’articolo stesso. Per realizzare l’obiettivo, l’Autrice, nella prima parte del lavoro, indica le carenze delle vigenti soluzioni legislative in materia e, nella seconda parte – le proposte per migliorarle. Il punto di riferimento per valutare e formulare le modifiche stesse è la normativa italiana. L’Autrice sollecita, tra l’altro, l’introduzione della definizione di agriturismo e l’introduzione di una definizione ampia di attività agricola, nella quale sia compreso anche l’agriturismo, nonché siano considerate altre attività di carattere non agricolo, comunque esercitate dall’imprenditore agricolo in connessione con l’attività agricola condotta in via principale. È altresì opportuna la modifica della normativa sulla vendita di prodotti agricoli trasformati direttamente nell’azienda agricola, nonché la previsione della riserva di denominazione „agriturismo” e la sistemazione delle norme giuridiche disperse in un’unica legge.